2021
DOI: 10.1007/s12325-021-01973-7
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Thromboembolic Events and Associated Healthcare Costs in Patients with Inflammatory Bowel Disease

Abstract: Introduction: Inflammatory bowel disease (IBD) is associated with greater risk of thromboembolic events (TEs) due to the link between systemic inflammation and hypercoagulability. This study assessed the rates of TEs among patients with IBD versus patients without immune-mediated disease (IMD) and the cost of TEs among patients with IBD in the United States.Methods: This study used the IBM MarketScan Ò Commercial and Medicare Supplemental Databases (2014Databases ( -2018. To assess the incremental rates of TEs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…5 A more recent study reported higher rates of deep vein thrombosis (DVT) (adjusted incidence rate ratio [IRR]: 2.44 [95% confidence interval [CI]: 2.00-2.99; p < 0.01) and pulmonary embolism (PE) (IRR: 1.90 [95% CI: 1.42-2.54]; p < 0.01) in patients with IBD. 6 The DVT risk appears to be similar in CD and UC: the reported incidence rate of DVT was 31.4/10,000 personyears and that of PE was 10.3/10,000 person-years in CD versus 30.0/10,000 person-years and 19.8/10,000 personyears in UC, respectively 4 (►Table 1).…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…5 A more recent study reported higher rates of deep vein thrombosis (DVT) (adjusted incidence rate ratio [IRR]: 2.44 [95% confidence interval [CI]: 2.00-2.99; p < 0.01) and pulmonary embolism (PE) (IRR: 1.90 [95% CI: 1.42-2.54]; p < 0.01) in patients with IBD. 6 The DVT risk appears to be similar in CD and UC: the reported incidence rate of DVT was 31.4/10,000 personyears and that of PE was 10.3/10,000 person-years in CD versus 30.0/10,000 person-years and 19.8/10,000 personyears in UC, respectively 4 (►Table 1).…”
mentioning
confidence: 89%
“…The incidence of VTE increases with age, and it is associated with active disease (defined as corticosteroid use) and hospitalization. 2 Although most studies found no significant sex-related differences in VTE incidence, it was recently reported that male sex may be associated with an increased risk of VTE-related hospitalization [6][7][8] ; the extent of the disease may also correlate with a higher VTE risk. 9 A retrospective study found pancolonic involvement in 76% of patients with UC and VTE, whereas colonic involvement, complicated disease (i.e., fistulas, stenosis, abscesses), and recent surgery were reported as risk factors for CD.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1 Interestingly, the reported risk of VTE is also high in certain otherwise benign conditions; patients with IBD have a 2-to 3-fold increased risk of DVT and pulmonary embolism (PE) compared with the general population. 20 In hospitalized patients with IBD, the overall risk of VTE has been reported to be 4.3%. [21][22][23][24] In a cohort study of 80,445 hospital discharges of patients with IBD, the cumulative rate of VTE at 12 months was 2.1% for patients with Crohn's disease (CD; 1.2% for surgical patients and 2.4% for nonsurgical patients; p < 0.001) and 2.0% for patients with ulcerative colitis (UC; 2.2% for surgical patients and 2.0% for nonsurgical patients; p = 0.32).…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Nevertheless, as a substantial amount of accumulated data suggests the safety and, to some extent, the beneficial effects of olive oil, it is well-justified to perform randomized trials that would confirm these effects and establish the appropriate dosage/type of olive oil in IBD treatment. An especially interesting aspect would be to determine the benefits, if there are any, of olive oil in the primary and secondary prevention of cardiovascular repercussions, as IBD patients are burdened by increased risk for atherosclerotic cardiovascular disease and venous thromboembolism [80,81].…”
Section: Evidence From Human Studiesmentioning
confidence: 99%